From Variables to Research Design: A Deep Dive into Educational Research Methodology - Adeoye, Moses Adeleke (LPPM Undiksha, 2023)
The systematic collection and analysis of data relevant to the field of education are referred to as educational research. Research writing is a laborious practice that methodically approaches the solution to a given research challenge. It differs from educational institutions and is typically led by a format. This study aims to analyze methodological explanation of variables, background to the study, literature review & research design as ways of promoting vigorous scholarship. This research uses the Systematic Literature Review (SLR) method. The results of this research explain many types of in-depth research methodology. These resources' main goal is to assist young academics and education professionals in learning about the background of the study, literature review, research design, and methodological explanation of variables. Educational research plays a crucial role in the development and improvement of educational practices and policies. It enables educators and policymakers to make informed decisions based on evidence and data. These offer beneficial fundamental knowledge for those who wish to pursue careers as researchers.